2019
DOI: 10.1177/1049731519864165
|View full text |Cite
|
Sign up to set email alerts
|

Perspective-Taking Interventions for Intergenerational Caregivers of Alzheimer’s Diseases: A Randomized Controlled Trial

Abstract: Purpose: The present study examined the effects of perspective-taking (PT) intervention in the context of intergenerational caregiving. Method: Seventy-two adult child caregivers of persons living with Alzheimer’s disease (AD) were randomized into two 8-week interventions: (1) connecting through caregiving (CTC: 37 participants) with intergenerational PT reappraisals and (2) basic skill building (BSB: 35 participants). The CTC intervention focused on PT reappraisals aiming to promote balance between self-care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 81 publications
(116 reference statements)
0
19
0
Order By: Relevance
“…Au et al (2019b) have found significant associations between generative behavior and positive emotions in older adults across three countries. Thus, aging-in-place has implications for life satisfaction not only for the older adults but also for the next generation (Au et al, 2019a;Oswald et al, 2011). The concept of the sense of community can provide a way of capturing the mechanism of change involved in building a more age-friendly community.…”
Section: Introductionmentioning
confidence: 99%
“…Au et al (2019b) have found significant associations between generative behavior and positive emotions in older adults across three countries. Thus, aging-in-place has implications for life satisfaction not only for the older adults but also for the next generation (Au et al, 2019a;Oswald et al, 2011). The concept of the sense of community can provide a way of capturing the mechanism of change involved in building a more age-friendly community.…”
Section: Introductionmentioning
confidence: 99%
“…Work by Haapala et al [15] on rural community services has indicated that both older customers and younger assistants might need education on each other's life-course priorities for the improved delivery of homebased support. Similarly, Au et al [16] have shown how supporting young carers through education on how to consider the perspective of the other (care recipient) can be beneficial to both parties. From the perspective of generational relations, commensal interaction around meals may provide a linking narrative across public and private spheres with the possibility of a space that allows for sharing, complementarity, and mutual learning.…”
Section: Institutional Enablers/risks Ageism and Age Segregation In Generational Relationsmentioning
confidence: 98%
“…The degree to which people become aware of this and their willingness to positively encounter the ageother indicates their degree of generational intelligence. Empirical work using generational intelligence has been undertaken by Haapala et al [15], Au et al [16] and Dow et al [3] to examine intergenerational relations in social work, education, and community settings. According to this model, any person or set of social arrangements can contain high or low degrees of generational intelligence.…”
Section: Generational Intelligence and Building Empathy In Intergenerational Commensalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Generational Intelligence framework, Dow et al, 7 found that positive intergenerational relations occurred much more easily in private, rather than in public spaces and that the public domain required forms of activation, such as those described by Kaplan et al, 8 Haapala et al, 9 study of rural community services, indicated that both older customers and younger assistants might need education on each other's life-course priorities to increase empathy in the improved delivery of home-based support. Similarly, Au et al, 10 have shown how supporting younger careers through education on how to take account of the perspective of the age-other (care-recipient), using a Generational Intelligence framework, can be beneficial to both parties.…”
Section: Introductionmentioning
confidence: 99%